Pengembangan Jiwa Kewirausahaan Pada Karang Taruna Kelurahan Cirendeu - Angga Pratama; Veta Lidya Delimah; Raden Roro Ayu Metarini (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2022)
The implementation of Community Service (PKM) is one of the applications of the Tri Dharma of Higher Education which in its implementation makes a positive contribution to the community. The implementation of this PKM takes the title "Development of the Entrepreneurial Spirit in Youth Organizations in Cirendeu Village". The location chosen is the Cirendeu sub-district which is located at Jalan Garuda No. 1, East Ciputat District, South Tangerang City, Banten. Where this location has youth organizations that require the development of a good entrepreneurial spirit. The method used in the implementation of this PKM is a Workshop or Training. Where previously the direct observation stage was carried out in order to find out the problems that arose at the research location. This training is used to provide an in-depth understanding of the development of an entrepreneurial spirit in the Cirendeu youth groups. The results of Community Service (PKM) went very smoothly and all participants who attended were ensured to get a fairly good understanding of the material. At the end of the training session, participants were also given simple practices to support the ability to implement the development of an entrepreneurial spirit which will be applied to the Cirendeu Village Youth Organization. As an improvement and ensuring the ability of participants to apply the material optimally, a periodic evaluation stage will be carried out from the team of lecturers and PKM teaching practitioners.